High HER2/Centromeric Probe for Chromosome 17 Fluorescence In Situ Hybridization Ratio Predicts Pathologic Complete Response and Survival Outcome in Patients Receiving Neoadjuvant Systemic Therapy With Trastuzumab for HER2‐Overexpressing Locally Advanced Breast Cancer. (9th December 2015) - Kogawa, Takahiro; Fouad, Tamer M.; Liu, Diane D.; Wu, Jimin; Shen, Yu; Masuda, Hiroko; Fujii, Takeo; Chavez‐MacGregor, Mariana; Alvarez, Ricardo H.; Hortobágyi, Gabriel N.; Valero, Vicente; Ueno, Naoto T.
Abstract : Background: The present study was performed to determine whether the human epidermal growth factor receptor‐related 2 (HER2)/centromeric probe for chromosome 17 fluorescence in situ hybridization (FISH) ratio is a predictor of a pathologic complete response (pCR), recurrence‐free survival (RFS), and/or overall survival (OS) in patients receiving neoadjuvant systemic treatment (NST) with trastuzumab (NST‐T) for HER2+ locally advanced breast cancer (LABC). Patients and Methods: The present retrospective study included 555 patients with HER2+ LABC who had undergone NST and definitive surgery (1999–2012); 373 had concurrently received trastuzumab. HER2‐positivity was considered present with an immunohistochemical score of 3+ and/or HER2 FISH ratio of ≥2.0. We used logistic regression analysis and Cox proportional hazard modeling to determine whether a high HER2 FISH ratio, either as a continuous variable or with a cutoff of ≥7.0, would predict for pCR (no invasive disease in the breast and no tumor in the ipsilateral axillary lymph nodes), RFS, and/or OS. Results: The pCR group's median HER2 FISH ratio was significantly higher than that of the non‐pCR group (6.4 vs. 5.2; p = .003). The logistic regression model demonstrated that the independent predictors of pCR included a high HER2 FISH ratio as a continuous variable ( p = .04). The multicovariate Cox proportional hazard model showed that a high HER2 FISH ratio (with a cutoff of ≥7.0 or as a continuous variable) was a significant prognostic indicator of longer RFS time ( p = .047 and p = .04, respectively). Similarly, a high HER2 FISH ratio of ≥7.0 was associated with longer OS ( p = .06). Conclusion: A high HER2 FISH ratio is a predictor of pCR in patients with HER2+ LABC who receive NST‐T. Implications for Practice: This study demonstrated the optimal predictive and prognostic value of a HER2/centromeric probe for chromosome 17 FISH ratio for primary HER2+ breast cancer treated with trastuzumab combined with neoadjuvant systemic treatment (NST‐T). This suggests that a high HER2 FISH ratio is a potential indicator for a high pathologic complete response rate and a better prognosis when patients are treated with NST‐T. Abstract : The present study has demonstrated that a high human epidermal growth factor receptor 2‐related fluorescence in situ hybridization ratio is a significant predictive factor for a pathologic complete response and recurrence‐free survival, with a favorable tendency to predict overall survival in patients with locally advanced breast cancer receiving neoadjuvant systemic treatment with trastuzumab.